Effect of Motivation and Discipline on Employee Performance at PT. XYZ - Sukarni Sukarni (Enrichment : Journal of Management, 2018)
The hypothesis in this study is that motivation and discipline affect the performance of employees at PT. Xyz. This study uses the basic theories of Human Resource Management related to motivation, discipline, and performance.The approach used in research is a survey method. The type of research conducted is quantitative descriptive. The nature of this research is explanatory. The population in this study all employees at PT. Xyz as many as 17 people. Samples taken throughout the population. The variables in this study are independent variables consisting of motivation (X1) and discipline (X2) and performance dependent variables (Y). The statistical test tool used to analyze the data in this study is multiple linear regression analysis. The effect of the independent variable on the dependent variable was tested by the F test and t test at a confidence level of 95% or significant level, α = 0.05. Data processing was performed using Statistical Package for Social Science (SPSS) 17.0 software. The results showed that motivation and discipline simultaneously and partially affected the performance of employees at PT. Xyz; Overall the effect of the independent variables (motivation and discipline) on the dependent variable (performance), motivation variables are more dominant influence on employee performance variables at PT.Xyz.